Wpływ działalności przedsiębiorstw na stan rynku dóbr konsumpcyjnych - Sołtysiak, Jan (Wydział Prawa i Administracji UAM, 1985)
Strategies of the trade enterprises' activities in the old economic and fiscal system were dominated by the resultant effects of the economic units producing consumption goods. Trade, distributing products among the consumers, generated ineffectiveness relations independent from producers by its own actions. That process was clearly manifested in the mechanism of self inducing and self consolidation of market disequilibrium. The trade apparatus was interested in realization of economic targets allowing maximization of employees' incomes and not improving effectiveness relations. At the same time profits, costs and marigin were adjusted in order to fufill directively fixed economic tasks. Introduction of new economic principles into our economy was intended to increase its effectiveness. In trade business the effects of the new system were to improve market supplies, service of customers and to influence radically the sphere of production. Yet it is apparent that new rules resulting from the existing system solutions are continuing to induce ineffectiveness reactions in trade. The trade apparatus is not interested in profits as a measure of economic effectiveness. The main subject of interest in the goods turn-over sphere is the maximization of income per one employee. No interest is revealed in the structure of sales and in the overall offer directed to the market with the account taken for consumer's interest. The latter is burdened with all consequences of ineffectiveness in the sphere of production and of trade.
Effect of the consumers' goods market on the activity of enterprises